Vascular Cerebral Anomalies Associated with Septo-Optic Dysplasia: A Case Report. Issue 1 (1st February 2013) - Chiaramonte, I.; Cappello, G.; Uccello, A.; Guarrera, V.; Damore, A.; Cavallaro, T.; Chiaramonte, R.; Ettorre, G.C.
We describe a case of Septo-Optic Dysplasia (SOD) characterized by the presence of anomalous cerebral vessels. In our young patient the classical features of SOD were associated with vascular anomalies including absence of the vein of Galen, right Rosenthal vein leading to the superior petrosal sinus, and anomalous origin of the anterior choroidal arteries. These findings have never been associated with SOD in the literature but their revelation supports the hypothesis of a vascular disruption as a possible cause of the SOD.